Conforming collections: assessing medical and allied health collections using Doody's Core Titles. - Torres Jr., Efren; Dery, Zipporah; Samar, Raquel; Gado, Marlon (Journal of the Medical Library Association, 2022)
This study assessed the print collection of an Asian academic medical library using list-checking. The library's book collection was matched to Doody's Core Titles (DCT) subspecialties to identify strong and weak subject areas and understand temporal trends from 2014 to 2020. Basic sciences and nursing were the strongest subspecialties from 2018 to 2020, with many subjects having 100% matches, likely because most academic programs share the same basic sciences foundation subjects and nursing collections had been developed for many years as a long-standing program of the institution. Associated health-related disciplines was the weakest subspecialty. These subjects need to be prioritized in collection development. All subspecialties exhibited an increasing trend of matching between 2014 and 2020. Electronic books were included in the matching to DCT 2020; however, the match was low compared to print only or both print and electronic titles. DCT title matching can not only identify gaps in library collections that need to be filled but also point toward opportunities to develop strong and varied collections in medicine and allied health.